Tindak Tutur Meminta dalam Film Kembang Api - Kulsum*, Lastunna Umi; Salsabiila, Fardha Yoedya; Putra, Gagas Roskadasya Indra; Azzahra, Kania Difia; Kifaya, Kinanti Nadia; Nugroho, Miftah (Universitas Suryakanca, 2024)
This article will describe the speech act of requesting in films